Investigating the Relationship Between Orthodontic Treatment and Temporomandibular Joint Disorders in Adolescents - Mohammad Khursheed Alam; Mohammad Younis Hajeer; Renad Atallah Alruwaili; Almas Ali Alfaleh; Ola Bassam Alhashash (Journal of Pharmacy and Bioallied Sciences)
Background: Orthodontic treatment is widely utilized to correct malocclusions and improve dental aesthetics in adolescents. However, its potential association with the development of temporomandibular joint disorders (TMDs) remains controversial. Materials and Methods: A prospective cohort study was conducted involving 200 adolescents aged 12–18 years undergoing orthodontic treatment. Participants were divided into two groups: those receiving fixed appliances (n = 150) and those undergoing aligner therapy (n = 50). The presence and severity of TMDs were assessed using the Research Diagnostic Criteria for Temporomandibular Disorders at baseline, 6 months, and 12 months post-treatment initiation. Data were analyzed using the Chi-square tests and multivariate logistic regression to identify potential risk factors. Results: At baseline, 10% of the total cohort exhibited mild TMD symptoms. After 12 months, 25% of the fixed appliance group showed an increase in TMD symptoms, compared to 15% in the aligner group. The logistic regression analysis revealed a significant association between the duration of treatment with fixed appliances and the development of TMDs (OR = 2.5; 95% CI: 1.2–5.1; P = 0.02). However, no significant correlation was found between aligner therapy and TMD incidence (OR = 1.1; 95% CI: 0.5–2.3; P = 0.67). Conclusion: The findings suggest that prolonged orthodontic treatment with fixed appliances may increase the risk of developing TMDs in adolescents, whereas aligner therapy appears to have a minimal impact on TMJ function.